2006
DOI: 10.1103/physrevb.74.245425
|View full text |Cite
|
Sign up to set email alerts
|

Controlled anisotropic deformation of Ag nanoparticles by Si ion irradiation

Abstract: The shape and alignment of silver nanoparticles embedded in a glass matrix is controlled using silicon ion irradiation. Symmetric silver nanoparticles are transformed into anisotropic particles whose larger axis is along the ion beam. Upon irradiation, the surface plasmon resonance of symmetric particles splits into two resonances whose separation depends on the fluence of the ion irradiation. Simulations of the optical absorbance show that the anisotropy is caused by the deformation and alignment of the nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 23 publications
6
105
0
Order By: Relevance
“…513,[666][667][668][669][670][671][672][673][674][675][676][677][678] The effect has been repeated in many systems, and as a general rule the results indicate that nanoparticles in a wide range of metals can be elongated with a suitable irradiation condition. Irradiation of 5 nm Ag nanoparticles in silica with 8 MeV Si ions ͑which does not have an energy deposition high enough to be considered a swift heavy ion͒, was based on indirect optical measurements reported to produce particles FIG.…”
Section: B Elongation Of Nanoclusters By Swift Heavy Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…513,[666][667][668][669][670][671][672][673][674][675][676][677][678] The effect has been repeated in many systems, and as a general rule the results indicate that nanoparticles in a wide range of metals can be elongated with a suitable irradiation condition. Irradiation of 5 nm Ag nanoparticles in silica with 8 MeV Si ions ͑which does not have an energy deposition high enough to be considered a swift heavy ion͒, was based on indirect optical measurements reported to produce particles FIG.…”
Section: B Elongation Of Nanoclusters By Swift Heavy Ionsmentioning
confidence: 99%
“…with a prolate shape. 668 Irradiation of 1-6 nm sized Au nanoparticles near the surface with 100 MeV Au ions was reported to lead to a growth in size. 670 However, because of the vicinity of the surface, part of the Au was also sputtered.…”
Section: B Elongation Of Nanoclusters By Swift Heavy Ionsmentioning
confidence: 99%
“…One is post-implantation treatment, such as annealing in different atmospheres [10] or ion irradiation. The embedded spherical NPs can be transfer to rodlike shape [11,12] or caused alignment of NP [13] by swift ion irradiation, which is leading to the anisotropic surface plasmon resonance of NPs. Although various models, like Coulomb explosion [14], viscoelastic model [15], ion hammering effect [16] and thermal spike model [17], are used as possible mechanisms to explain the change, the exact mechanisms responsible for NC shape transformation still need to be further investigated.…”
Section: Controlling the Size And Distribution Of Nanoparticlesmentioning
confidence: 99%
“…On the other hand, Giulian et al 9 reported that Pt NPs with a diameter above the threshold value become progressively elongated with increasing fluence, with the length of the smaller axis saturating at approximately this threshold value. Olivier et al 10 investigated the ion-shaping mechanism for embedded Ag NPs. Penninkhof et al 11 investigated the ion-shaping of Au NPs confined within a planar silica matrix under irradiation with 30 MeV Si ions.…”
Section: Introductionmentioning
confidence: 99%